Unsur Sinematik dalam Membentuk Genre Found Footage pada Film Keramat Karya Monty Tiwa - Muzakki, Muhammad Ariq; Pradhono, Choiru; Adriyandi, Adriyandi (ROLLING, 2023)
This study aims to reveal and determine the role of cinematic elements contained in found footage genre films. The formation of the found footage genre contained in the film, seen from the aspects of mise en scene (setting, lighting, makeup and costumes as well as players and movements), cinematography, sound and editing. The research method used is a qualitative research method with a descriptive approach. The object of research chosen was the Sacred (2009) by director Monty Tiwa. Data in the study were obtained from observation, literature studies and documentation about films. The theory used in analyzing cinematic elements is the theory of cinematic elements by Himawan Pratista based on the theory of found footage by Alexandra Heller and Nicholas. The results of this study showed that 22 scenes were selected as objects identifying cinematic elements in forming the found footage genre. In this film, cinematic elements play an important role in supporting the packaging of found footage horror genre films so that they can build audience confidence in reality and suspense through mise en scene, cinematography, sound and editing. Acting players and subjective cameras with long-duration handheld camera techniques on films, giving greater influence to the realistic impression of found footage genre films. Keywords: Cinematic Elements, Genre Found Footage, Sacred Film.